Clinician perspectives and experiences in the prescription of ankle-foot orthoses for children with cerebral palsy. (1st February 2019) - Kane, Kyra; Manns, Patricia; Lanovaz, Joel; Musselman, Kristin
ABSTRACT: Purpose : Physiotherapists, orthotists, and physicians are involved in the prescription of ankle-foot orthoses (AFOs) for children with cerebral palsy (CP); however, little is known about how prescription decisions are made in practice. Therefore, the study objective was to identify current AFO prescription and clinical decision-making practices for children with CP in Canada. Methods : Focus groups were conducted in five pediatric rehabilitation facilities, with 32 clinicians. Semi-structured interviews focused on the goals and types of AFOs used, referral and follow-up processes, and clinical evaluation measures. Interpretive Description was used as a framework for analysis. Transcribed dialogue was imported into NVivo 11 for data coding and analysis. Three researchers participated in coding to establish categories and themes. Results : Categories included: what is made, how it is used, and factors that either support or challenge outcomes. Strengths and challenges of the current prescription process were discussed, including funding, communication, and technology to enhance clinical evaluation. Throughout the interviews, the theme of prescription as a collaborative, iterative, and individualized process emerged. Conclusions : Processes, strengths, and challenges associated with AFO prescription in Canada were identified. This is a first step toward the development of guidelines to help clinicians improve AFO prescription for children with CP.